THE PKSN STRATEGY (NATIONAL STRATEGIC ACTIVITIES CENTER) BASED ON GRAND DESIGN OF STATE BORDERS MANAGEMENT - Johnson, Posma Sariguna Johnson; L.Tobing, Suzanna Josephine; Heatubun, Adolf Bastian; Lumbantoruan, Rutman (Universitas Kristen Indonesia, 2018)
Central and local governments face various obstacles in realizing National Strategic Activities Center (PKSN) development. This paper aims to review it, by conducting normative studies. We study various literature and regulations issued by the government. Many of the problems in the field that must be considered. They are the absence of concrete minimum requirements related to border services within the city PKSN, the absence of incentives / disincentives to development programs